Australian mean land-surface temperature. (March 2018) - Haynes, Marcus W.; Horowitz, Frank G.; Sambridge, Malcolm; Gerner, Ed J.; Beardsmore, Graeme R.
Highlights: A mean land-surface temperature map of the Australian continent was produced from 13 years of MODIS satellite imagery, for the period 2003–2015. The results show good agreement with independent methods of estimating average land-surface temperature. In comparison to previously used methods of estimating mean land-surface temperature, our new estimates are up to 12 °C warmer. The map provides spatially continuous estimates of land-surface temperature that can be incorporated as the surface thermal boundary condition in geothermal studies. Abstract: The mean land-surface temperature represents an important boundary condition for many geothermal studies. This boundary is particularly important to help constrain the models made to analyse resource systems, many of which are shallow in nature and observe relatively small thermal gradients. Consequently, a mean land-surface temperature map of the Australian continent has been produced from 13 years of MODIS satellite imagery, for the period 2003–2015. The map shows good agreement with independent methods of estimating mean land-surface temperature, including borehole surface-temperature extrapolation and long-term, near-surface ground measurements. In comparison to previously used methods of estimating mean land-surface temperature, our new estimates are up to 12 °C warmer. The MODIS-based method presented in this study provides spatially continuous estimates of land-surface temperature that can be incorporated as the surface thermal boundary condition in geothermal studies. The method is also able to provide a quantification of the uncertainties expected in the application of these estimates for the purposes of thermal modelling.